2015
DOI: 10.3174/ajnr.a4317
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Core Needle Biopsy and Its Impact on Surgical Management in Patients with Medullary Thyroid Cancer: Clinical Experience at 3 Medical Institutions

Abstract: BACKGROUND AND PURPOSE:Medullary thyroid carcinoma is an uncommon malignancy that is challenging to diagnose. Our aim was to present our experience using core needle biopsy for the diagnosis of medullary thyroid carcinoma compared with fine-needle aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 34 publications
1
34
1
1
Order By: Relevance
“…When thyroid lymphoma or anaplastic cancer is suggested, CNB is preferable to FNA in many studies (16404142). A recent study suggested a role for CNB in medullary thyroid carcinoma (43). …”
Section: Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…When thyroid lymphoma or anaplastic cancer is suggested, CNB is preferable to FNA in many studies (16404142). A recent study suggested a role for CNB in medullary thyroid carcinoma (43). …”
Section: Indicationsmentioning
confidence: 99%
“…Core needle biopsy has been reported to be useful for the specific diagnosis of some malignant thyroid lesions, especially lymphoma, anaplastic carcinoma, and medullary carcinoma (16264379). Both anaplastic thyroid cancer and thyroid lymphoma can be present as rapidly growing thyroid masses in elderly patients (80).…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoon et al [58] used a new sampling technique [18] in order to validate that CNB is more useful than FNA for diagnosing follicular neoplasms. CNB is reportedly helpful for diagnosing rare thyroid malignancies such as lymphoma and anaplastic and medullary carcinomas [5,17,[59][60][61][62].…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…This tumor is resistant to external beam radiotherapy and shows poor response to chemotherapy. Hence, surgery is the only strategy for potential treatment [1,4,5]. However, for a successful surgical attempt, one should be familiar with site and extent of disease [6].…”
Section: Introductionmentioning
confidence: 99%